2015
DOI: 10.1016/j.jmoneco.2014.11.011
|View full text |Cite
|
Sign up to set email alerts
|

Capital flows and the risk-taking channel of monetary policy

Abstract: 3Adjustments in bank leverage act as the linchpin in the monetary transmission mechanism that works through 4 fluctuations in risk-taking. In the international context, we find evidence of monetary policy spillovers on cross-5 border bank capital flows and the US dollar exchange rate through the banking sector. A contractionary shock to US 6 monetary policy leads to a decrease in cross-border banking capital flows and a decline in the leverage of international 7 banks. Such a decrease in bank capital flows is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
611
4
6

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 893 publications
(660 citation statements)
references
References 44 publications
39
611
4
6
Order By: Relevance
“…Avdjiev et al (2015) criticize the "triple coincidence" assumption in the conventional paradigm for monetary economics, i.e., that the GDP boundary coincides with the monetary policy decision-making unit and currency area, for neglecting the effects of international currencies on domestic financial stability. Based on country-level data, Bruno and Shin (2015b) show how US monetary policy spills over to cross-border bank capital flows through fluctuations in banks' risk-taking behavior, amplifying the leverage cycle in the foreign banking sector. On the aggregate level, Rey (2015) finds that the monetary policy of the US affects the leverage of global banks, which leads to co-movements of global asset prices and cross-border capital flows, and credit growth in the international financial system; this results in an "irreconcilable duo" -independent monetary policy is only possible if and only if the capital account is managed.…”
Section: Introductionmentioning
confidence: 99%
“…Avdjiev et al (2015) criticize the "triple coincidence" assumption in the conventional paradigm for monetary economics, i.e., that the GDP boundary coincides with the monetary policy decision-making unit and currency area, for neglecting the effects of international currencies on domestic financial stability. Based on country-level data, Bruno and Shin (2015b) show how US monetary policy spills over to cross-border bank capital flows through fluctuations in banks' risk-taking behavior, amplifying the leverage cycle in the foreign banking sector. On the aggregate level, Rey (2015) finds that the monetary policy of the US affects the leverage of global banks, which leads to co-movements of global asset prices and cross-border capital flows, and credit growth in the international financial system; this results in an "irreconcilable duo" -independent monetary policy is only possible if and only if the capital account is managed.…”
Section: Introductionmentioning
confidence: 99%
“…There is an active and in ‡uential empirical literature, for example, Neely (2010), Gagnon et al (2011), Krishnamurthy and VissingJorgensen (2011), trying to assess the e¤ects of the QE program on interest rates, expected in ‡ation, and other asset prices such as exchange rates. 9 A major approach in this literature is to assess the "announcement e¤ects" of such policies, the response of high-frequency …nancial variables to the Federal Reserve's announcements of policy changes within a very narrow time frame such as one or two days. By isolating the changes in these variables due to the announcement of QE policy, this literature has shown that such policies most likely contributed to lowering long-term interest rates and depreciating the US dollar.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, both innovations in the global monetary policy stance (MP) and risk factor disturbances (RF) deepened the U.S. trade imbalance since the early 2000s, while portfolio allocation shifts (PA) and terms of trade shocks (TT) had a partially offsetting effect. The worsening of Td determined by monetary policy shocks accords with the basic mechanism of the international risk-taking channel of monetary policy (Borio and Zhu 2012;Bruno and Shin 2015): over-expansionary U.S. monetary policy caused a contraction in perceived risk and funding costs, fuelling asset prices and the net worth of financial institutions, as well as their leverage and risk-taking attitude, resulting in capital inflows into the U.S. and depreciation of the US$.…”
Section: Global Imbalances Liquidity and Financial Marketsmentioning
confidence: 99%